Development of a Silver-Based MOF Oxidase-Like nanozyme modified with molecularly imprinted polymer for sensitive and selective colorimetric detection of quercetin - Karrat, Abdelhafid; Benssbihe, Jihane; Mohammad Ameen, Sameera Sh; Omer, Khalid M.; Amine, Aziz (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2025)
[Display omitted] •A new Ag-MOF with oxidase-like activity is developed.•The Ag-MOF nanozyme exhibits a catalytic efficiency of 0.19 µmol min−1 mg−1.•The integration of MIP onto Ag-MOF ensures selective detection of quercetin.•The Ag-MOF@MIP nanozyme detects quercetin with a LOD of 0.43 μM. Antioxidants are vital components in various food, plant, and pharmacological products, making their quantitative, selective, and straightforward assessment essential for evaluating product quality and health benefits. Nanozymes, such as metal–organic frameworks (MOFs) with enzyme-like catalytic activity, hold significant potential for developing highly efficient antioxidant sensing platforms. This is due to their large specific surface area, low density, high porosity, structural diversity, and adjustable pore size. In this study, we synthesized a silver-based MOF exhibiting effective oxidase-like activity and modified it with molecularly imprinted polymer (MIP) using radical polymerization. The developed system (Ag-MOF@MIP) was successfully applied for the colorimetric detection of quercetin, achieving a limit of detection of 0.43 μM and a limit of quantification of 1 μM within a detection range of 1 to 132 μM. This combination exhibited improved selectivity and sensitivity towards quercetin and demonstrated high stability after one month of storage. This detection strategy can also be used to detect other analytes using TMB as a probe.